Dynamics of Priacanthus hamrur (Forsskal)exploited off Saurashtra coast - Kizhakudan, Shoba Joe; Zala, M S (Indian Journal of Fisheries, 2011)
Bull’s eye landings off Saurashtra reached a peak of 3813 tons in 1999 with acatch rate of 4.3 kg per haul. The group is represented by a single species,Priacanthus hamrur (Forsskal). Gut content analysis revealed P. hamrur to bea carnivorous fish with a preference for pelagic crustaceans and fishes. Spawningfemales were encountered from March to December and the length at firstmaturity of female P. hamrur was 198 mm. Recruitment to the fishery takesplace with two peaks annually - one in January-February  and a minor one inOctober-November. A common length-weight relationship for both sexes wasobtained with a = 3.481x105 and b = 2.83498. The von Bertalanffy growthequation was derived as Lt = 360.35 [1-e-0.56(t+ 0.1013)] and the length attained bythe  fish at the end of 1 to 4 years were estimated as 165, 249, 296 and 324 mm.The length  growth performance index was obtained as !’ = 4.86 and thelongevity, tmax was  estimated as 4.44 years. The mortality co-efficient Z, M andF were 2.35, 1.14 and 1.21, respectively and exploitation rate, E was 0.51. Stockassessment studies reveal that the present average annual catch can be increasedby 764 t to reach the MSY of 4996 tons.